Desenvolvimento de procedimentos em fluxo envolvendo reatores em fase sólida e microssistema analítico construído com LTCC (Low Temperature Co-fired Ceramics) para a determinação de analitos de interesse farmacêutico - Suarez, Willian Toito (2009)
The employment of flow injection systems to determination of N-acetylcysteine, captopril, dipyrone and fluoxetine hydrochloride in pharmaceutical formulations was investigated. The N-acetylcysteine was determinated employing a solid-phase reactor containing Zn3(PO4)2 immobilized in a polyester resin coupled to a flow injection system. The procedure was based on the chelation of Zn(II) ions with N-acetylcysteine in the solid-phase reactor, with consequent releasing of the complex Zn(II)-N-acetylcysteine of the reactor, this complex reacted with alizarin red S (VA) in borate buffer pH 9.0 generating the complex Zn(VA-BO3)3 which absorbance was measured spectrophotometrically at 540 nm. The second developed procedure was the determination of captopril (CAP) in pharmaceutical formulations employing a solid-phase reactor containing silver chrolanilate (Ag2C6Cl2O4) immobilized in a polyester resin. In this system occured the precipitation reaction of captopril with the Ag(I), producing in the reactor an insoluble salt between the CAP and the Ag(I) due to the lower solubility of the formed salt related to Ag2C6Cl2O4. After the formation of the insoluble salt in the reactor occured the releasing of chloranilate anion, C6Cl2O4 2-, that reacted with the Fe(III) producing the complex FeC6Cl2O4 + which was monitored spectrophotometrically at 528 nm. In another procedure, the N-acetylcysteine and captopril were determined separately in a flow injection system through the on-line of the Prussian blue formation. In this procedure, the N-acetylcysteine or the captopril were oxidized by Fe(III), producing Fe(II) that reacted with hexacyanoferrate(III) in a point of flow system, generating the Prussian blue (Fe4[Fe(CN)6]3), that was monitored spectrophotometrically at 700 nm. It was also proposed a flow injection system with merging zones and intermittent flow with turbidimetric detection to determination of fluoxetine hydrochloride in pharmaceuticals. This system was based on the formation of an insoluble salt (AgCl(s)) between the AgNO3 and the chloride of the hydrochloride of the fluoxetine molecule that was turbidimetrically detected at 420 nm. Finally, two procedures were developed employing a flow injection system to determination of dipyrone in pharmaceuticals using Fe(III) as chromogenic reagent. In the first procedure, it was employed an analytical microsystem constructed with LTCC and in the second one, it was used a flow injection system with merging zones without the use of microsystem. In these systems, occured the formation on-line of an blue chromophore between Fe(III) and the dipyrone that was monitored spectrophotometrically at 622 nm.